Evaluation of disparities in the incidence, presentation, and treatment of pediatric differentiated thyroid cancer in the United States (2000–2022) - Xuejuan Ning; Rong Wang; Jennifer Ogilvie; Catherine Dinauer; Xiaomei Ma; Nicole C. Deziel (PLoS ONE, 2025)
Introduction Rates of pediatric differentiated thyroid cancer (DTC) have been increasing, yet disparities in incidence, diagnosis, and treatment across race and ethnicity have not been fully explored. Methods We assessed temporal trends in the incidence of pediatric DTC using data from 2000–2022 (excluding 2020 due to COVID-19) from the National Childhood Cancer Registry. Annual percent changes (APC) were calculated using joinpoint regression analysis overall and by race, ethnicity, age, and clinical factors. Differences in cancer presentation and treatment by race and ethnicity were evaluated using data from Surveillance, Epidemiology, and End Results (SEER) for 18 registries for 2006–2018, while accounting for socioeconomic status (SES). Results Overall pediatric DTC incidence increased 4.5% annually from 2000−2018 (95%CI: 3.8%−5.8%), then declined (−6.9%) through 2022 (95%CI: −14.5%, −1.2%). Rates of decline appeared sharpest among Non-Hispanic White patients. Incidence rates continued increasing among Non-Hispanic Asian/Pacific Islanders and patients diagnosed with tumors >4 cm. Compared to non-Hispanic White patients, non-Hispanic Black, non-Hispanic Asian/Pacific Islander, and Hispanic children were more likely to be diagnosed with a tumor >4 cm. Conclusion Declines in reported pediatric thyroid cancer incidence, particularly among the smallest tumor sizes, after 2018 may be attributable to application of thyroid cancer management guidelines. However, the continued increase among those presenting with larger tumor sizes may support a true continued increase in incidence among some groups. The greater proportion of non-White children being diagnosed with larger tumors could be due to inequities related to timely access to care, differential application of thyroid management guidelines, differences in cancer subtypes, or other factors. These findings warrant further exploration when additional years of data are available.